Mastering the potter's wheel : techniques, tips, and tricks for potters - Carter, Ben, 1980- (2016)
"A book of advances wheel techniques and inspiration for potters who have basic skills but would like to learn more about throwing large forms, lids, handles, darting, and more"--
The Basics -- Building Wheel Skills -- Making Lids, Knobs, Handles, and Spouts -- Setting the Table -- Altering Pots-- Throwing Large -- Decorating and Finishing.
Includes bibliographical references and index.
Keywords: Pottery -- Technique; Potters' wheels; CRAFTS & HOBBIES / Pottery & Ceramics; CRAFTS & HOBBIES / Reference